Sustainable Use of Waste Tire Rubbers in Eco-Friendly and Lightweight Alkali-Activated Slag–Silica Fume Mortars - Dheyaaldin, Mahmood Hunar; Bayraktar, Oğuzhan Yavuz; Öz, Ali; Kaplan, Gökhan (American Society of Civil Engineers (ASCE), 2024)
This study examines the benefits of substituting waste tire aggregate (WTA) for pumice aggregate in alkali-activated slag mortars at replacement ratios of 0% to 60% (by volume). Additionally, silica fume (SF) was added to mortar mixes at a concentration of 10% by volume to improve their compressive and flexural strength, water absorption, water sorptivity, porosity, density, thermal conductivity, and microstructural properties. The influences of chemical sulfate attacks, exposed temperatures, and compressive strength were investigated. Test findings showed that using WTA severely decreased mechanical strength and durability. Conversely, a mixture with 60% WTA reacted at a lower strength and durability compared with different percentages of WTA for all the properties examined in this study. SF has led to significant enhancements in mechanical strength and durability, especially at an early age. On the eighth day of the specimen curing period, the compressive and flexural strength increased by 20%. Additionally, by raising the curing temperatures by 80°C enhances the polymerization process, the polymerization process is strengthened, boosting durability characteristics and improving mechanical strength and durability. When exposed to higher temperatures, the mechanical strength and durability reduced the specimens' strength and weight. Specimens exposed to sulfate attack solutions can reduce the mechanical strength by 1%-3% for a 120-day curing period in a chemical solution, even more reducing the weight of specimens and shapes after visual inspection.